2008
DOI: 10.1074/jbc.m802517200
|View full text |Cite
|
Sign up to set email alerts
|

Lysosome Dispersion in Osteoblasts Accommodates Enhanced Collagen Production during Differentiation

Abstract: Lysosomes are essential organelles for intracellular degradation and are generally sequestered near the cell center to receive vesicles with contents targeted for destruction. During ascorbic acid (AA)-induced differentiation of osteogenic cells (Beck, G. R., Jr., Zerler, B., and Moran, E. (2001) Cell Growth Differ. 12, 61-83), we saw a marked increase in total lysosome organelles in osteoblastic cells, in addition to an enhanced endocytic rate. Interestingly, lysosomes were dispersed toward the cell periphery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…Such functional roles for Ostm1 are supported by our dynamic studies that showed intracellular organelle dispersion and protein corelocalization. Since both Ostm1 and KIF5B are ubiquitously expressed in a wide range of cells, this interaction could underlie a general cellular mechanism where Ostm1 in a complex with KIF5B would transport and deliver key molecules by trafficking to organelles or to specific sites within cells (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Such functional roles for Ostm1 are supported by our dynamic studies that showed intracellular organelle dispersion and protein corelocalization. Since both Ostm1 and KIF5B are ubiquitously expressed in a wide range of cells, this interaction could underlie a general cellular mechanism where Ostm1 in a complex with KIF5B would transport and deliver key molecules by trafficking to organelles or to specific sites within cells (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…The high representation of cathepsins in cluster 1 indicates a role of lysosomal protein degradation during osteoblastic differentiation of MSC. A marked increase in total lysosome organelles and endocytosis in osteoblastic cells as well as implication of lysosomes in procollagen processing has been reported (79).…”
Section: Functional Annotation Of Proteins In the Four Clusters Suggementioning
confidence: 99%
“…Since an increase in lysosomal pH leads to the inhibition of lysosomal hydrolases, this could dramatically affect the ability of these cells to process and degrade engulfed material [32], [36]. Indeed, using a self-quenched DQ-ovalbumin particle system, we confirmed that the decreased acidification of lysosomes of CHM patients significantly affected proteolytic abilities of the monocytes [25], [26]. Monocytes from different CHM patients demonstrated significant variation in the rates of uptake of material, lysosomal acidification and protein degradation, which could be explained by the effects of different mutations in the CHM gene on structure and function of REP-1.…”
Section: Discussionmentioning
confidence: 58%
“…Ovalbumin conjugates are internalized via the mannose receptor–mediated endocytosis pathway and are recognized by antigen-presenting cells [25], [26]. The increase in fluorescence corresponding to the rate of degradation of engulfed DQ-ovalbumin was measured using FACS analysis at different time points following the feeding period.…”
Section: Methodsmentioning
confidence: 99%